Evolución de la Alianza del Pacífico entre 2015 y 2020 (2020)
The Pacific Alliance is an integration agreement composed of Mexico, Chile, Peru and Colombia, was created in order to achieve free trade in goods, services, people and capital between member countries, adding to this agreement the facility to trade and establish relations with countries in Asia Pacific and over time achieve trade relations with different integrations of Asia. This integration agreement has been evolving in a satisfactory way for the member countries, thanks to the fact that the evolution of the agreement is reflected within the related countries and these have been able to promote different factors such as, the exploration and increase of new markets, the increase in the export of products, the growth of the SMEs, the increase in the rate of tourism, among other things, this has had the effect of having several countries outside the agreement interested in being able to enter and relate to these four countries and thus promote a young integration that has an important potential.